Thai military power a culture of strategic accommodation - Raymond, Gregory Vincent (Monograph series, 2018)
Thailand remains important by virtue of its location at the centre of the Asia-Pacific region, an area playing a vital role in world affairs. And yet, although Thailand has a comparatively large population and has powerful military forces performing significant roles in state and society, the country itself is seen as having little military power; it is a minor player. Why is this?0Using strategic culture as an analytical framework, this book produces a portrait of the Thai state as an accommodative actor. During the period of Western imperial dominance in Asia, Thailand `bent in the wind' to preserve its independence by a limited trading of territory and sovereignty. This accommodative policy continues to the present day in different forms. A key feature is that military organisational culture reinforces a state ideology of royalist nationalism that in turn reinforces the national strategic culture